Characterization of adsorption and desorption of lawn herbicide siduron in heavy metal contaminated soils. (August 2018) - Jiang, Rong; Wang, Meie; Chen, Weiping
Abstract: Siduron is a widely used herbicide in urban lawn and has been frequently detected in urban and suburban surface water. However, characteristics of its environmental behavior in soil are seldom reported. The combined pollution of heavy metals, especially for Cu, Pb, Cd, Zn and siduron would be common because of the widely existence of heavy metal pollution in urban soils. In this study, four soils with similar physicochemical properties but different levels of preexisting heavy metals were selected to investigate the adsorption and successive desorption of siduron using batch experiments. The results revealed a low sorption of siduron to all the tested soils. The organic carbon normalized distribution coefficient ( K oc ) of siduron in the studied soils ranged from 117 to 137 L kg −1 and was not significantly correlated to heavy metal levels. No apparent desorption hysteresis was observed with the hysteresis index ( HI ) ranging from 0.921 to 1.11. More than 50% of the sorbed siduron was readily released into soil solution. Results suggested that siduron was highly mobile and bioavailable in the studied soils. Significant correlation was found between adsorption/desorption parameters and soil organic carbon (SOC) in four soils. soil organic matter was thus considered as the dominant factor determining the adsorption and desorption of siduron in soils. Different from most of reported studies conducted by laboratory-amended soils, the influence of preexisting heavy metals on the adsorption-desorption of siduron was not significant in this work. Highlight: Siduron was lowly adsorbed by the studied soils with the K oc ranging from 117 to 137. No apparent hysteresis was observed and the sorbed siduron was readily desorbed into soil solution. Soil organic matter was the dominant factor affecting the behavior of siduron in soils. Heavy metal contamination did not significantly impact siduron sorptive behavior in soils.